Persaingan Kekuasaan Antara India dan Cina : Dari Kekuasaan Militer Sampai Dengan Konflik Siber - Refika Febrianti; Abubakar Eby Hara; Bagus Sigit Sunarko (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
This article aims to analyze the development of power competition between China and India from military competition to cyberspace and the reasons why India in 2020 expanded this conflict area to cyberspace. This expansion of competition is marked by India's ban on Chinese mobile applications. The research was conducted using a qualitative research approach and literature study methods as well as the theory of Struggle for Power, Cyber power and cyber Sovereignity. The discussion of this paper shows the main reason why India brings conflict to cyberspace by banning Chinese mobile application was because India had to restrain China’s rising dominance in cyber power. The ban was come under a longstanding power and influence rivalry of both countries. India is tend to left behind and suffered several defeats in conventional millitary competition with China. Afterward, the cyber rivalry allows India to have an extensive opportunity in restraining China’s power. Keywords: China, cyber sovereignity, India, cyber conflict, struggle for power